Mass Transfer in CO2 Huff-Puff of Shale Oil Reservoirs - Yang, Zijiang; Zeng, Haikun (Scientific Journal of Technology, 2025)
Experimental study on the influencing factors of CO2 injection to enhance oil recovery in shale oil reservoirs using nuclear magnetic resonance (NMR) technology. The effects of action time, pressure, and temperature on enhanced oil recovery were analyzed based on the NMR T2 (transverse relaxation time) spectrum, and the oil displacement effect of CO2 on crude oil was observed through NMR images. Then, molecular dynamics simulation methods were used to study the interaction laws and mass transfer characteristics between crude oil and carbon dioxide under different conditions, and the results of macroscopic experiments were analyzed using the insights obtained from microscopic simulations. The study shows that during the CO2 injection process, the recovery degree gradually increases with the extension of the action time. As the pressure increases, the recovery degree gradually rises. With the increase in temperature, the recovery degree of shale oil first increases and then gradually decreases. Under immiscible conditions, the recovery degree of crude oil in macropores increases rapidly with the increase of injection pressure; under miscible conditions, the impact of increased injection pressure on the recovery degree of macropores weakens. Regardless of miscibility, the recovery degree of crude oil in micropores basically shows a linear growth with the increase of injection pressure, and as the gas injection pressure increases, the lower limit of CO2-accessible pore size continues to decrease. With the increase of soaking time, the growth rate of crude oil recovery degree in macropores gradually decreases, while the growth rate of crude oil recovery degree in micropores first increases and then decreases.